2019
DOI: 10.1111/asj.13321
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of ensiling characteristics and protein degradation of alfalfa silage prepared with corn or sweet sorghum in semiarid region of Inner Mongolia

Abstract: Alfalfa (Medicago sativa L.), a valuable supplemental protein feed for livestock, is one of the most common legume grasses in the world (DiCostanzo et al., 1999). Northern China is a major alfalfa production area, but despite the synchronization of the rainy season and harvesting, haymaking is difficult in some regions. Therefore, practices ensuring long-term preservation of high-quality alfalfa need to be developed. Silage fermentation and storage for alfalfa are considered the most effective technologies for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 57 publications
2
11
1
Order By: Relevance
“…The lower CP content in Group 2 might due to the increased proteolysis activities after adding cellulase and starch during fermentation, but the specific synergy mechanism among them remained unknown till now. Tao et al [ 25 ] also observed similar results in alfalfa when ensiled with sweet sorghum. Previous studies have demonstrated that cellulase application to silage materials can improve fermentation quality by decreasing the NDF and ADF contents during ensiling [ 26 - 28 ].…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…The lower CP content in Group 2 might due to the increased proteolysis activities after adding cellulase and starch during fermentation, but the specific synergy mechanism among them remained unknown till now. Tao et al [ 25 ] also observed similar results in alfalfa when ensiled with sweet sorghum. Previous studies have demonstrated that cellulase application to silage materials can improve fermentation quality by decreasing the NDF and ADF contents during ensiling [ 26 - 28 ].…”
Section: Resultsmentioning
confidence: 58%
“…Effects of applying additives on fermentation characteristics of Napier grass silageControl: no additives; Group 1: added cellulase; Group 2: added cellulase and starch; NH3-N: ammonium nitrogen; TN: total nitrogen; LA: lactic acid; AA: acetic acid; PA: propionic acid; BA: butyric acid; Flieg' s scores (0-100) were ranked into five grades: Poor (0-20), Fair(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), Average (41-60), Good (61-80), and Excellent (81-100); '-': default.…”
mentioning
confidence: 99%
“…In each bottle, 20 g of silage was blended with 180 mL deionized water and stored at 4 • C for 24 h [16]. The mixture was then filtered through four layers of cheesecloth to determine the fermentation parameters.…”
Section: Silage Chemical Composition Determinationmentioning
confidence: 99%
“…Ensiling is typically the most effective and economical method to preserve fresh forage grass and it can improve palatability and prolong the maximum storage duration via anaerobic fermentation [11,12]. For silage fermentation, the low dry matter (DM) content (19.9%), the low water-soluble carbohydrates (WSC) content (2.52% DM), and the low level of epiphytic lactic acid bacteria (LAB, <10 5 colony-forming units (CFU)/g fresh matter (FM)) of fresh CLL make it difficult to ensile [12].…”
Section: Introductionmentioning
confidence: 99%